2021
DOI: 10.1186/s12870-020-02787-5
|View full text |Cite
|
Sign up to set email alerts
|

Response of phytohormone mediated plant homeodomain (PHD) family to abiotic stress in upland cotton (Gossypium hirsutum spp.)

Abstract: Background The sequencing and annotations of cotton genomes provide powerful theoretical support to unravel more physiological and functional information. Plant homeodomain (PHD) protein family has been reported to be involved in regulating various biological processes in plants. However, their functional studies have not yet been carried out in cotton. Results In this study, 108, 55, and 52 PHD genes were identified in G. hirsutum, G. raimondii, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 78 publications
0
12
0
Order By: Relevance
“…Therefore, their expression in different plant tissues has also attracted much attention. Studies have shown that the expression patterns of the PHD gene family in different species are concentrated in different tissue types ( Sun et al., 2017 ; Qin et al., 2019 ; Wu et al., 2021 ). Most of them have a high level of expression in reproductive organs, including rice ( Sun et al., 2017 ) and potato ( Qin et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, their expression in different plant tissues has also attracted much attention. Studies have shown that the expression patterns of the PHD gene family in different species are concentrated in different tissue types ( Sun et al., 2017 ; Qin et al., 2019 ; Wu et al., 2021 ). Most of them have a high level of expression in reproductive organs, including rice ( Sun et al., 2017 ) and potato ( Qin et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ethylene-responsive factors (ERFs) belong to a subfamily of the AP2/ERF superfamily which is involved in tomato response to the pathogens P. syringae pv. tomato ( He et al, 2001 ) and Stemphylium lycopersici ( Yang et al, 2021 ), among others.…”
Section: Discussionmentioning
confidence: 99%
“…GhPHDs genes are involved in regulating cotton growth and development, particularly ovule and fiber development. It has been noted that GhPHDs genes (especially GhPHD5, GhPHD80, and GhPHD88) respond well to various phyto-hormone signal transduction pathways and enhance cotton tolerance to different stresses, including salt, heat, and drought [145]. Wu et al [145] showed that phyto-hormones improved plant tolerance to abiotic stresses via GhPHD genes and their co-factors, but their regulatory mechanisms and interaction network still need to be further investigated.…”
Section: Role Of Ga and Sa Synthase Genes In Salt Stress Tolerancementioning
confidence: 99%
“…It has been noted that GhPHDs genes (especially GhPHD5, GhPHD80, and GhPHD88) respond well to various phyto-hormone signal transduction pathways and enhance cotton tolerance to different stresses, including salt, heat, and drought [145]. Wu et al [145] showed that phyto-hormones improved plant tolerance to abiotic stresses via GhPHD genes and their co-factors, but their regulatory mechanisms and interaction network still need to be further investigated. The expression GhPHD5 genes has been significantly increased after treatments of MeJA (Methyl jasmonate), IAA (Indole-3-acetic acid), and BL (brassinolide).…”
Section: Role Of Ga and Sa Synthase Genes In Salt Stress Tolerancementioning
confidence: 99%